PRUNING AND ORGANIC FERTILIZER RESPONSE GRANUL (POG) ON THE GROWTH AND PRODUCTION OF WATERMELON (Citrullus vulgaris Schard) - Suryawaty Suryawaty; Toto pertowo (AGRIUM: Jurnal Ilmu Pertanian, 2015)
The purpose of this study was to evaluate the response of organic fertilizer granules (POG) and pruning on the growth and production of watermelon (Citruluss Schard vulgaris). This research use Random Divided (RPT) consisting of two factors namely Pruning studied (P) as the main plots and Organic Fertilizer granules (G) as a subplot, for this study using two factor without trimming (P0) and pruning (P1 ), for a dose of organic fertilizer granules are G0 (without treatment), G1 (1.5 kg / plot), G2 (3 kg / plot) and G3 (4.5 kg / plot), there are 8 combination treatment was repeated 3 times produce 24 units experiment with a whole number of plants per plot 384 plants where 5 plants with plant samples 3 plants and has 72 plant samples to the whole. The parameters observed were plant height, flowering age, harvesting age, number of fruit crops, the number of perplot fruit, fruit diameter planting, planting fruit weight, fruit weight perplot. The results showed that treatment without pruning significant effect on the number of fruit per plot, while pruning effect on growth of watermelon on the largest fruit diameter 45.10 cm while for the production of more 10.25 fruit without pruning. Organic fertilizer granules while not affect the growth of watermelon, while the largest fruit production 46.44 cm, 2.97 kg and the heaviest pieces of fruit per plot toughest 21.43 kg. Interactions between factors organic fertilizer granules (POG) and pruning showed significantly different results.Keywords: pruning, organic fertilizer granules (POG), watermelon production and growth